Testing of pandemic ventilators under early and agile development - Tachatos, Nikolaos; Steffen, Nicola; Zander, Mark; Stankovic, Nikola; Meboldt, Mirko; Erb, Thomas O.; Hammer, Jürg; Schmid Daners, Marianne (Frontiers in Medical Technology, 2022)
Aiming to address clinical requirements subsequent to the SARS-CoV2 related pulmonary disease, multiple research groups and industry groups started intensive efforts to develop pandemic ventilators (PDVs). In vitro testing to critically evaluate the specific performance of the developed apparatuses is an essential requirement. This study presents a test protocol which promotes a test-oriented, iterative and agile assessment and consecutive development of such PDVs. The test protocol includes an evaluation of the accuracy of control systems and instruments at changing parameters, the oxygen dynamics and the response to trigger signals. The test environment is a mechanical lung which permits to reproduce various lung mechanics and to simulate active breathing cycles. Three PDVs which are under development were iteratively tested as well as a Hamilton T1 as a reference. The test protocol presented allows for fast identification of specific characteristics of each PDV in the individual test features. Continuous testing of the PDVs under development allows for a quick identification of critical application aspects that deserve further improved. Based on the present test protocol, the ventilators present a promising performance justifying further continued development.